Anti-Candida albicans IgG Antibodies in Children With Autism Spectrum Disorders - Hughes, Heather K.; Ashwood, Paul (Frontiers in Psychiatry, 2018)
The gut microbiota are known to have a profound influence on both mucosal and systemic immunity and are important for gastrointestinal (GI) function. In addition, new evidence shows that the microbiota significantly influence neurodevelopment and behavior. Immune dysfunction and GI distress are extremely common in individuals with autism spectrum disorders (ASD). A growing body of evidence suggests that individuals with ASD have significant aberrations in the composition of their gut microbiota, known as dysbiosis. However, these studies have focused on the bacterial components of the microbiota, leaving the fungal microbiota in ASD poorly studied. Increases in fungal species such as Candida albicans are associated with inflammatory bowel disorders, and have recently been implicated in several neurological disorders including schizophrenia. We aimed to determine if children with ASD exhibit elevations in antibodies that target C. albicans, indicating current or previous overgrowth of this fungal species. We measured anti-C. albicans immunoglobulin (IgG) in plasma from 80 children enrolled in the UC Davis MIND Institute CHARGE study. Measurements were acquired using a commercial ELISA kit. Plasma anti-C. albicans antibody positivity was found in 36.5% (19/52) of children with ASD. Anti-C. albicans antibodies in typically developing controls was (14.3%; 4/28). Overall, ASD children had a higher rate of high-positive values compared to typically developed children with an unadjusted odds ratio of 3.45 (95% confidence interval, 1.0409 to 11.4650; p = 0.041, two-tailed). GI dysfunction was found in about half of the ASD children who were positive for anti-Candida IgG. This study provides evidence of a new microbial risk factor for ASD.